Application of fluorescence correlation spectroscopy to investigate the dynamics of a ribosome-associated trigger factor in Escherichia coli - Niwa, Tatsuya; Nakazawa, Koki; Hoshi, Kensuke; Tadakuma, Hisashi; Ito, Koichi; Taguchi, Hideki (Frontiers in Molecular Biosciences, 2022)
Co-translational protein folding is one of the central topics in molecular biology. In Escherichia coli, trigger factor (TF) is a primary chaperone that facilitates co-translational folding by directly interacting with nascent polypeptide chains on translating ribosomes. In this study, we applied fluorescence correlation spectroscopy (FCS), which can analyze the diffusion properties of fluorescent molecules by measuring the fluctuations of the fluorescent intensity, to investigate the interaction between TF and a nascent chain on translating ribosomes both in vitro and in vivo. The FCS analysis with a reconstituted cell-free translation system revealed that the interaction of fluorescently labeled TF with a nascent chain depended on the emergence of the nascent chain from the ribosome exit tunnel, and this interaction was not inhibited by excess amounts of other chaperones. Furthermore, the translation-dependent interaction between GFP-fused TFs and nascent chains was also observed in living E. coli cells. The FCS-based approach established here could be an effective method to investigate the dynamics of other ribosome-associated chaperones besides TF.